Species Diversity and Germplasm Collection of Medicinal Plants from Eastern Ghats - Pandravada, S. R.; Sarath Babu, B.; Sivaraj, N.; Rao, G. Maheswara; Satyanarayana, Y. V. V. (Indian Forester, 2000)
An exploration was undertaken during December, 1997 in the Eastern'Ghats for the collection of medicinal, aromatic and dye yielding plants, Out of 207 accessions of germplasm collected 150 are medicinal, 14 are aromatic, 18 are dye yielding and the rest belong to different agri-horticultural crops and wild species. The species diversity in medicinal plants collected belongs to 40 dicotyledonous and eight monocotyledonous plant families. In dicotyledons, the maximum number of genera belong to family Fabaceae and the maximum number of species belong to genus Solanum. In monocotyledons, the family Zingiberaceae is represented by a maximum number offour genera and five species. The medicinal utility of the germplasm is also highlighted.